BEYOND FRIENDSHIP: UNDERSTANDING THE ROLE OF COST IN GIFT CHOICES FOR ONESELF AND OTHERS - Kim, Hyung Jun; Jun, Jongkun; Kim, Jooyoung (PEOPLE: International Journal of Social Sciences, 2024)
This study explores how social closeness and self-identification influence the monetary value of gifts chosen for friends and for oneself. Integrating the Self-expansion Model with Resource Scarcity Theory, we provide insights into consumer behavior in gift selection under varying social and financial contexts.